Placer of agates at Vertikalny Cape, Eastern Kamchatka - Савельев Д.П. (Bulletin of Kamchatka Regional Association «Educational-Scientific Center». Earth Sciences, 2020)
In the area of the city of Petropavlovsk-Kamchatsky, field work was carried out, which included routes through hard-to-reach bays along the coastal cliffs of Avachinsky Gulf. Agates and chalcedony were collected in a boulder and pebble placer southwest of Cape Vertikalny. Their source is volcanic strata of the Zavoikovsky Complex of the Miocene age. Ornamental stones are observed among the pebbles and boulders of volcanics. Gray monochromatic chalcedony and low-contrast agates prevail among them, but there are also agates with a contrasting and complex pattern, as well as «moss» and «landscape» agates. The length of the coastal placer, separated by rocky cliffs, is about 2 km. Some agates have inclusions of native copper, from a fraction of mm and rarely up to 5 mm in size, which is of interest for mineral collectors.